Production of Biosynthesized Silver Nanoparticles using Metarhizium anisopliae fungus for the Treatment of Petroleum Pollutants in Water (Baghdad Science Journal, 2024)
In this study, a silver nanoparticle (AgNPs) was created using a biological technique from an extract of the fungus Metarhizium anisopliae. The characteristics of the prepared AgNPs were identified by utilizing the optical, ultraviolet, and infrared absorbance spectroscopy. The shape, size, and charge distribution on the particles were determined by using scanning electron microscopy and zeta voltage analysis. The analysis of biological activity of the silver nanoparticles showed its effectiveness in treating pollutants, as confirmed by the reduction of higher than 93% weight of crude oil in contaminated water samples. The crude oil mass was effectively transformed into the gelatinous mass that lacks consistency and emulsification. The chemical analysis of NP-treated and untreated crude oil- contaminated water samples was performed using gas chromatography mass spectrometry (GC MASS). The results displayed the emergence of 55 graphic peaks, each of them indicating a chemical compound, in the control sample, while in the study sample, about 51 of these peaks disappeared and the area of the remaining 4 peaks was reduced. The silver nanoparticles' capability to maintain their effectiveness under cryogenic storage conditions for six months was tested and compared to that of the fungal isolation before the production of the silver nanoparticles. The results showed no significant changes in the shape, size, and efficiency of the silver nanoparticles in the treatment of oil pollutants in water. The results indicated the higher efficiency of the silver nanoparticles, as compared to chemicals, in treating petroleum pollutants as well as enhancing the solubility, emulsification, and degradation of hydrocarbons.  In addition, the AgNPs are characterized by the availability of inexpensive, easy, fast to produce, and environmentally friendly production materials, as compared to the usage of chemical products that are highly toxic to aquatic organisms, expensive to produce, and highly accumulative in the ecosystem, i.e. environmentally unsafe.